Outcomes and prognostic factors after pulmonary metastasectomy in patients with colorectal cancer with previously resected hepatic metastases - Shimizu, Kimihiro; Ohtaki, Yoichi; Okumura, Takehiro; Boku, Narikazu; Horio, Hirotoshi; Takenoyama, Mitsuhiro; Yamashita, Motohiro; Hyodo, Ichinosuke; Mori, Keita; Kondo, Haruhiko (The Journal of thoracic and cardiovascular surgery, 2019)
Outcomes and prognostic factors remain obscure in patients with colorectal cancer after pulmonary metastasectomy who had previously received a curative hepatic metastasectomy. We collected data of 757 patients with pulmonary metastasis from colorectal cancer who underwent curative metastasectomy between 2004 and 2008 from 46 Japanese institutions, from which we extracted data on patients who previously received curative hepatic metastasectomy. Disease-free survival, overall survival, and prognostic factors were analyzed. The subjects of this study were 160 patients, of whom 44% had primary rectal tumor, 73% had a single pulmonary metastasis, 11% had a bilateral pulmonary metastasis, and 39% had high (>5 ng/mL) serum carcinoembryonic antigen. Patients' median age was 66 years, and 58% were male. The median follow-up was 64 months. Five-year overall survival and disease-free survival were 65.2% (95% confidence interval, 56.8-72.5) and 33.5% (95% confidence interval, 26.1-41.0), respectively. In multivariable analyses, high prethoracotomy carcinoembryonic antigen level was an independent prognostic factor for overall survival (hazard ratio, 2.01; 95% confidence interval, 1.16-3.47) and disease-free survival (hazard ratio, 2.10; 95% confidence interval, 1.41-3.12). Five-year overall survival and disease-free survival of patients with normal prethoracotomy carcinoembryonic antigen level were 76.4% (95% confidence interval, 66.1-83.9) and 40.7% (95% confidence interval, 30.5-50.5), respectively. After pulmonary metastasectomy, approximately two thirds of patients with colorectal cancer with a history of curative hepatic metastasectomy survived for 5 years—half of them disease-free. Our results indicate that patients with colorectal cancer with pulmonary metastasis and a history of curative hepatic metastasectomy may benefit from sequential pulmonary metastasectomy, especially if prethoracotomy serum carcinoembryonic antigen levels are within normal range. [Display omitted]